Srategibauran Pemasaran Dalam Meningkatkan Penjualan Batik (Study Kasus pada Rumah Batik Koperasi Adikarya Probolinggo Sejahtera) - Riska Wulandari; Abu Yazid Adnan Quthny; Nuntufa Nuntufa (STIE AMKOP, 2023)
This study aims to analyze the marketing mix and sales turnover at the batik house in the Adikarya Probolinggo Sejahtera Cooperative. In carrying out the marketing mix and the efforts made to increase batik sales in the Adikarya Probolinggo Sejahtera Cooperative. This study used a qualitative approach and took the research location at the Adikarya Cooperative Batik House, Probolinggo Sejahtera. The subjects of this study were the leaders of the Adikarya Probolinggo Sejahtera Cooperative Batik House and employees. Data collection was carried out using interview, observation, and documentation methods. Researchers conducted research assisted by interview guidelines. The data analysis technique used is the presentation of data. The results of the study show that the Adikarya Probolinggo Sejahtera Cooperative has carried out effective marketing, by conducting a marketing mix consisting of several components, namely products that are varied and of high quality, setting reasonable prices not emphasizing prices that are too high, selecting locations in strategic areas, in terms of promotions have used various methods such as on social media (whatsapp, instagram etc.) and exhibitions, have experienced and professional staff so that they can increase sales effectively, and provide loyalty to consumers, as well as adequate company support facilities. In addition, the Adikarya Probolinggo Sejahtera Cooperative is the only Batik House that provides batik raw materials for Serobolinggo batik makers. Keywords: Strategy marketing mix increasing sales